High‐Performance Thermally Conductive Phase Change Composites by Large‐Size Oriented Graphite Sheets for Scalable Thermal Energy Harvesting - Wu, Si; Li, Tingxian; Tong, Zhen; Chao, Jingwei; Zhai, Tianyao; Xu, Jiaxing; Yan, Taisen; Wu, Minqiang; Xu, Zhenyuan; Bao, Hua; Deng, Tao; Wang, Ruzhu (Advanced materials (Weinheim), 2019)
Efficient thermal energy harvesting using phase‐change materials (PCMs) has great potential for cost‐effective thermal management and energy storage applications. However, the low thermal conductivity of PCMs (KPCM) is a long‐standing bottleneck for high‐power‐density energy harvesting. Although PCM‐based nanocomposites with an enhanced thermal conductivity can address this issue, achieving a higher K (>10 W m−1 K−1) at filler loadings below 50 wt% remains challenging. A strategy for synthesizing highly thermally conductive phase‐change composites (PCCs) by compression‐induced construction of large aligned graphite sheets inside PCCs is demonstrated. The millimeter‐sized graphite sheet consists of lateral van‐der‐Waals‐bonded and oriented graphite nanoplatelets at the micro/nanoscale, which together with a thin PCM layer between the sheets synergistically enhance KPCM in the range of 4.4–35.0 W m−1 K−1 at graphite loadings below 40.0 wt%. The resulting PCCs also demonstrate homogeneity, no leakage, and superior phase change behavior, which can be easily engineered into devices for efficient thermal energy harvesting by coordinating the sheet orientation with the thermal transport direction. This method offers a promising route to high‐power‐density and low‐cost applications of PCMs in large‐scale thermal energy storage, thermal management of electronics, etc. A method for synthesizing high‐performance thermally conductive phase‐ change composites is demonstrated. Large aligned graphite sheets inside the composite are generated from worm‐like expanded graphite. The aligned and interconnected graphite framework enhances KPCM up to 4.4–35.0 W m−1 K−1 at graphite loadings below 40.0 wt%, which may accelerate the high‐power‐density, low‐cost, and large‐scale applications of phase‐change materials.